Caregiver Health by Context: Moderating Effects of Mental Health and Health Behaviors. (July 2021) - Longacre, Margaret L.; Brewer, Benjamin; Hubbard, Adeline; Ashare, Rebecca L.; Patterson, Freda
This study assessed caregivers' perceptions of their physical health by care context and explored the moderating role of mental health and health behaviors. This a cross-sectional, secondary analysis using de-identified Behavioral Risk Factor Surveillance System survey data. Deficits in mental health and engaging in healthier behaviors was associated with an increased odds of experiencing at least one week of poor physical health or being in a fair or better health category, respectively. Differences in the odds were noted according to care context (i.e., reason for care). For example, with each unit increase in mental health score (worse mental health), the odds of experiencing at least one week of poor physical health increased among cancer caregivers at about one-and-a-half times as compared to old age caregivers (p=0.006). Findings suggest that some caregiving groups derive less benefit from positive health behaviors, while some groups are more adversely impacted by poorer mental health.